Flow characteristics of inclined rectangular nozzles - Singaraveloo, Dineswaran. (2013)
A study has been embarked to understand the flow characteristics and dynamics of inclined rectangular nozzle. It is already an established fact that inclined non-circular nozzles are known for its enhanced jet entrainment properties and mixing characteristics. With numerous studies performed on non-circular nozzles such as the inclined elliptic nozzles, much less was known about the inclined rectangular nozzle. Laser Induced Fluorescence (LIF) Flow Visualisation displayed the formation of coherent structures and its subsequent behaviour. Some behaviours were found to be similar with that of other inclined non-circular nozzles. These include the increasingly severe turning in of vortex roll-ups with increasing nozzle inclination; the betterment of flow coherency with increasing nozzle inclination; and the increasingly deteriorating rib structures along major planes with increasing nozzle inclination. However, some unique behaviourial features of the inclined rectangular nozzles have been identified. The apparent lack of initial vortex pairing, delays in the onset of jet column narrowing, higher disparity in the asymmetric Reynolds shear stress distribution between the longer nozzle length and its shorter counterpart are some of the major unique features. Digital Particle-Image Velocimetry (PIV) is also performed to further quantify the findings in terms of vorticity contour, velocity vector and Reynolds shear stress contour maps. Further studies were conducted on the controlled perturbation of the inclined rectangular jet flows. It was discovered that the preferred mode of excitation lies between the Strouhal values of 0.5 and 0.7 for the inclined rectangular nozzle as compared with 0.4 for the inclined elliptic nozzle. The comparisons of the jet spread deformation in both planes reveal a delayed onset of axis switching for the inclined rectangular nozzle.